Total Quality Management (TQM) pada Lembaga Pendidikan: Review Sistematik atas Tren, Tantangan, dan Implikasi Praktis - Kamilatun Khoiriyah; Erina Dwi Hapsari; M. Salman Alfarizi; Mu’allimin Mu’allimin (Jurnal Manajemen Bisnis Era Digital, 2025)
Integrated Quality Management (IQM) or Total Quality Management (TQM) has become a strategic issue in the field of education because it is directly related to improving the quality of learning, school management, and the achievement of sustainable competency standards. In the context of Islamic education and integrated schools, the implementation of IQM is not only oriented toward managerial efficiency but also toward the integration of religious values and the development of students’ character. Therefore, this literature review is essential to understand the development, trends, and challenges of IQM implementation in education. The purpose of this literature review is to examine how IQM is applied in various educational institutions and to identify its theoretical and practical contributions. The research questions proposed are: (1) How are the concepts and principles of IQM developed in education? (2) What are the main impacts and challenges of its implementation? The study employed a literature search through repositories, e-journals, and online publications using the keywords “integrated quality management,” “TQM,” and “education.” Out of 20 initial articles, only 5 met the inclusion criteria and were analyzed in depth. The analysis results revealed three main themes: strengthening the fundamental concepts of IQM, the role of key figures and TQM principles in education, and the implementation impacts on academic and non-academic quality. In conclusion, IQM has proven to be relevant as a strategy for improving educational quality, although challenges such as limited resources and internal resistance still need to be addressed. Future research should explore adaptive IQM strategies tailored to the local school context.